Guinea pig versus computer mouse in post graduate practical pharmacology - Rodrigues, Allen Joe; Kamath, Laxminarayana (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pressures from animal right organizations like PETA lead to stringent animal handling guidelines by CPCSEA, UGC, MCI which resulted in limitation of animal experiments in postgraduate practical pharmacology. So, this study is designed to know the perceptions and alternative suggestions of pharmacology postgraduate students about animal experiments in their practical curriculum. Methods: 127 pharmacology postgraduate students who participated southern regional conference of IPS -2016 at Belgaum, Karnataka were included in this questionnaire based study. The data was analysed using descriptive statistics. Results: Majority 79% students favoured animal experiments even though only 53% of students were conducting animal experiments at their institute. Some of the reasons quoted by the students to favour animal experiments were, provide better understanding of drug effects (66%), interested in preclinical research & drug development (60%), provides hands on experience (56%) etc. Some of the virtual experiments suggested by students which can be used in parallel to animal experiments to reduce animal sacrifice were computer simulated animal experiments (78%), preformed graphs/charts (65%), video films (53%) and so on. Main reasons to like CAL were effects of drug can be clearly visualized (72%), can be repeated (63%), avoids error (57%), saves time (54%) etc. Conclusions: There is a need to incorporate CAL along with continuation of animal experiments in postgraduate practical pharmacology, so that both will compliment, enhance, reinforce the learning from each other and also drastically reduce the number of animals sacrificed.